Ketika kasih sayang menjadi belenggu: konsep diri dan pola asuh permisif indulgent sebagai prediktor cinderella complex pada mahasiswi - Darmawan, Atthoriq; Arya, Lutfi; Syanti, Wanda Rahma (Fakultas Psikologi Universitas Hang Tuah, 2026)
Cinderella Complex is a psychological construct describing women's tendency toward psychological dependency on external protective figures, systematically impeding self-actualization. This study examined the simultaneous and partial contributions of self-concept and permissive-indulgent parenting style to Cinderella Complex tendency among female university students. A quantitative non-experimental predictive design was employed with 80 active female students (aged 18–25 years) from six universities in Surabaya, recruited via accidental sampling. Instruments included the Cinderella Complex Tendency Scale (α = .965), the Self-Concept Scale (α = .978), and the Permissive-Indulgent Parenting Scale (α = .966). Multiple linear regression analysis revealed that both predictors simultaneously and significantly predicted Cinderella Complex (F(2,77) = 224.803, p < .001, R² = .854). Partially, self-concept was the stronger predictor (β = .724, p < .001) compared to permissive-indulgent parenting (β = .231, p = .004). These findings indicate that intervention programs should prioritize positive self-concept reconstruction alongside balanced parenting education to reduce psychological dependency among women in emerging adulthood.